Yaws in the Philippines: first reported cases since the 1970s - Belen Lardizabal Dofitas; Sherjan P. Kalim; Camille B. Toledo; Jan Hendrik Richardus (BMC, 2020)
Abstract Background Yaws is a chronic, highly contagious skin and bone infection affecting children living in impoverished, remote communities and caused by Treponema pallidum subspecies pertenue. The Philippines was thought to be free of yaws following the 1950s eradication campaign but it has been reported in the Liguasan Marsh area, Central Mindanao. This is the first documentation of yaws cases in the Philippines since the 1970s. We describe active and latent yaws recently detected in the Southern Philippines. Case presentation Cross-sectional surveys and screening of skin diseases were conducted in one randomly selected public elementary school per selected municipality in Liguasan Marsh, covering three municipalities per province. Yaws suspects underwent screening and confirmatory serologic tests for Treponema pallidum using Dual Path Platform Syphilis Screen and Confirm Assay (DPP) and Treponema pallidum Particle Agglutination (TPPA). Children with yaws skin lesions and reactive confirmatory tests for T. pallidum and non-treponemal antibodies were considered confirmed yaws cases. Four children aged 5-10 years old had confirmed secondary yaws in Tulunan Municipality, Cotabato Province and in Lambayong Municipality, Sultan Kudarat Province. All had secondary yaws lesions such as moist, cauliflower-like papillomas, thick yellow crusts on pink papules and nodules, whitish, papulosquamous papules and plaques, or hypopigmented patches with small papules on the periphery. Yaws papillomas and erosions were also found on the soles of the feet of one child. The index case had a skin punch biopsy of a partially treated papilloma on his axilla. Histopathological findings showed lichenoid psoriasiform dermatitis with plasma cells, consistent with yaws. Conclusions The clinical, serological, and histopathological confirmation of four yaws cases among children has made the Philippines the 14th country endemic for yaws. This report can help health personnel recognize hidden cases of yaws based on skin signs and serological tests. Yaws remained unrecognized and unreported in the Philippines and in countries previously endemic for yaws probably due to the unsustained integration of the yaws program in the general health services and complacency after the 1950s eradication campaign. Our findings have provided the necessary evidence and stimulus to develop a yaws control and eradication program as one of the country's neglected tropical diseases.